Ensuring sufficient cabin hospital beds for curbing the spread of COVID-19 – Findings from petri net analysis. Issue 10 (October 2022) - Chen, Chen; Xing, Zijie; Xi, Yonghui; Tiong, Robert
Abstract: Due to the complexity of the virus and its rapid rate of spread, many countries face the same challenges of providing adequate medical resources. This paper provides an analytical approach for evaluating the possibility of the regional construction industry constructing a large number of cabin hospitals within a short time. The key idea is to compare the demand and supply of patient beds using a Petri net-based approach that incorporates a neural network for the prediction of demand, fuzzy logic for decision-making, and a linear model for predicting supply. The data reported in the Shanghai Omicron battle is used to validate the developed model. Our results show that the fastest conversion speed and the least manpower requirement are obtained from high-rise buildings. Then, preparing some high-rises for easy conversion into cabin hospitals seems a possible solution for future citywide preparedness toward pandemic resilience. Graphical abstract: Image 1 Highlights: A Petri net analytical tool for studying cabin hospital demand and supply. The case of the Shanghai Omicron outbreak. Sensitivity analysis for the impact of manpower and impact of venue size. Vertical cabin hospitals are recommended to build post-pandemic resilience. Abstract : Cabin hospital; COVID-19; Demand and supply; Petri-net; Prediction.